As metamorfoses no espaço com o advento da Copa do Mundo no Brasil: estudos sobre o distrito de Itaquera-SP - Santos, William Jorge Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The present work discuss the reproduction of the social relations from the point of view of the new urban production relations - having as empirical universe for analysis-, the Itaquera district in the Sao Paulo metropolis, with the advent of the World Cup in Brazil. Starting with the reading of a reality in movement, in which the analysis walks covering the dialectic relationship between space and society, where the first is translated into product and life reproduction condition, aiming to unveil the metamorphoses that will take place in the urban space with its consequent contradiction, what it may be the expanded capital reproduction concomitantly with the process that denounces a spoliation movement of the social space. With the society approval before these big architectural projects enabled by ideology, it’s determined the (re) production of artificial spaces of consumption, funded for the capital extension. The current stage that the capitalism reveals a space turned into mass consumption merchandise, consequence of the victory of the exchange value over the usage value, amalgamated in positive measures of expulsion/sweeping of low income socio-economic layers

O presente trabalho discute a reprodução das relações sociais na ótica das novas relações de produção no urbano - tendo como universo empírico de análise-, o distrito de Itaquera na metrópole de São Paulo, com advento da Copa do Mundo no Brasil. Partindo da leitura de uma realidade em movimento, na qual a análise caminha abarcando a relação dialética entre espaço e sociedade, onde o primeiro se traduz em produto e condição de reprodução da vida, objetiva-se desvelar as metamorfoses que ocorrerão no espaço urbano com sua consequente contradição, qual seja a reprodução ampliada do capital concomitantemente ao processo que denuncia um movimento de espoliação do espaço social. Com a aprovação da sociedade diante destes grandes projetos arquitetônicos possibilitados pela ideologia, determina-se a (re) produção de espaços artificiais de consumo, financeirizados para ampliação do capital. O atual estágio que o capitalismo revela um espaço tornado mercadoria de consumo massificado, consequência da vitória do valor de troca sobre o valor de uso, amalgamado em medidas positivas de expulsão/varredura de camadas socioeconômicas de baixa renda
Keywords: Espaço urbano; Espaço em economia; Copa do mundo (Futebol); Geografia urbana - São Paulo (SP); Capital (Economia); Itaquera (SP); Public spaces; Space in economics; World cup (Soccer)